N-Demethylsinomenine, an active metabolite of sinomenine, attenuates chronic neuropathic and inflammatory pain in mice - Zhou, Zhiyong (Sci Rep, 2021)
Chronic pain is a significant public health problem that afflicts nearly 30% of the global population, but current pharmacotherapies are insufficient. Previous report indicated that N-demethylsinomenine, an active metabolite of sinomenine, is efficacious against postoperative pain. The present study investigated whether N-demethylsinomenine is effective for chronic painful conditions or whether repeated treatment alters its effect. Both chronic constriction injury (CCI) surgery and complete Freund’s adjuvant (CFA) intraplantar injection induced significant and reliable mechanical allodynia at least for 7 days. Acute treatment with N-demethylsinomenine (10–40 mg/kg, i.p.) dose-dependently attenuated the mechanical allodynia both in CCI-induced neuropathic pain and CFA-induced inflammatory pain in mice. The potency of N-demethylsinomenine for reducing CFA-induced mechanical allodynia was slightly higher than sinomenine. During the period of repeated treatment, N-demethylsinomenine maintained its anti-allodynic effect against both neuropathic and inflammatory pain without producing carry-over effect. Pretreatment with bicuculline, a selective γ-aminobutyric acid type A (GABA(A)) receptor antagonist, almost completely blocked the anti-allodynia of N-demethylsinomenine (40 mg/kg) both in CCI and CFA-treated mice. Our findings indicated that N-demethylsinomenine exhibits GABA(A) receptor-mediated anti-allodynic effects in mouse models of neuropathic and inflammatory pain, suggesting it may be a useful novel pharmacotherapy for the control of chronic pain.